Experimental investigation of recycled machining coolant mixed with nanofluids based Al2O3 - S. K., Lim; N. Z., Mohamad; A. R., Yusoff (IOP Publishing, 2019)
Machining coolant is used in manufacturing industry for lubrication, rusting control and cooling which are crucial in operations such as grinding and cutting process. However, the machining coolant lose efficiency in months due to the thermal degradation and contamination. To recycle the used of machining coolant while enhancing the performance, the mixture of nanofluids (N) based Al2O3 with better thermal properties to synthesize with the recycled machining coolant (RMC). This study suspended Al2O3 nanofluids in four base ratios of recycled machining coolant (i.e. 0:100, 20:80, 40:60 and 60:40) by ultrasonic homogenies. The three main parameters in cooling rate performance and rusting control are thermal conductivity, dynamic viscosity and pH indication, respectively. The thermal conductivity and dynamic viscosity are then measured at temperature range of 30 to 60°C. The highest enhancement of thermal conductivity was evaluated to be 37.9% higher than machining coolant base fluid at the temperature of 60°C in 60:40 (N:RMC). However, the enhancement of dynamic viscosity was measured to be 4.5% for 60:40 (N:RMC) at 60°C. The pH value of 60:40 (N:RMC) at ambient temperature obtained 8.18 value was nearly neutral and decreased the rusting process. Therefore, this study recommends the use of recycled machining coolants based Al2O3 as cutting fluid in the ratio of 60:40 for application in machining operations.